2010
DOI: 10.1177/070674371005500308
|View full text |Cite
|
Sign up to set email alerts
|

Age of Onset of Cannabis Use is Associated with Age of Onset of High-Risk Symptoms for Psychosis

Abstract: Cannabis use or a cannabis use disorder at a younger age in a group with an UHR for transition to psychosis is related to onset of high-risk symptoms for psychosis at a younger age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 32 publications
5
44
2
1
Order By: Relevance
“…Cannabis use is known to be a risk factor for SPE (Miettunen et al, 2008;Dragt et al, 2010). Alcohol abuse has received less attention, despite comparable rates of cannabis and alcohol abuse in people with schizophrenia (Cantor-Graae et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cannabis use is known to be a risk factor for SPE (Miettunen et al, 2008;Dragt et al, 2010). Alcohol abuse has received less attention, despite comparable rates of cannabis and alcohol abuse in people with schizophrenia (Cantor-Graae et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to a greater number of traumas is associated with a higher risk of psychosis Spauwen et al, 2006). Cannabis use is also associated with SPE (Miettunen et al, 2008;Dragt et al, 2010). Houston et al (2008) found an interaction between cannabis use, childhood sexual abuse, and adult non-affective psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…Between August 2002 and April 2006, data were collected from 245 help-seeking patients (age [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] who met Ôultra-high riskÕ (UHR) and ⁄ or Ôcognitive disturbancesÕ (COGDIS) criteria and agreed to participate in the European Prediction of Psychosis Study, EPOS (22,23). EPOS is a European collaboration of six centers in four countries: Germany, Finland, the Netherlands, and England.…”
Section: Recruitmentmentioning
confidence: 99%
“…The first cannabis use usually occurs during early ages and, development and the severity of cognitive dysfunction is related with early starting age 15 . During adolescence period, the higher potential for developing addiction or the more severe addiction may be related with this.…”
Section: Introductionmentioning
confidence: 99%